A disguised hydride in a butylmagnesium cation. Issue 45 (21st May 2018) - Banerjee, Sumanta; Ankur,; Andrews, Alex; Venugopal, Ajay
Abstract : The reactivity of a butylmagnesium cation provides a new perspective on the concept of β-hydride abstraction in s-block chemistry. Abstract : The ability of the β-CH functionality in a butylmagnesium cation [Me6 TREN–Mg– n -Bu] + to quantitatively reduce benzophenone has been demonstrated. The hydridic nature of the β-CH functionality is highlighted by its abstraction using B(C6 F5 )3 . β-CH abstraction over alkylation in [Me6 TREN–Mg– n -Bu] + is dependent on the nature of the incoming electrophile and the polarity of the solvent.